Rancang Bangun Aplikasi Penentuan Harga Pokok Produksi Berdasarkan Biaya Taksiran Pada UMKM Sepatu Dan Sandal Suroso - Farah Priminta Arumsari; Arifin Puji Widodo; Anjik Sukmaaji (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Micro, Small and Medium Enterprises (SMEs) Shoes and Sandals Suroso strive to improve and develop the industry, one of the efforts is to find out information about the costs of production are used to determine the cost of goods manufactured correctly. Currently, SMEs do not have a basis in determining the cost of goods manufactured according to customer order. In determining the cost of goods manufactured, SMEs just do a sum the raw material cost and direct labor cost, without counting the factory overhead cost. The resulted of the selling price of shoes and sandals are charged to customers is not as expected by the SMEs, so the profit can get unstable then. Because these problems, the author makes an application that can calculate the cost of goods manufactured is based on estimated cost by determining the raw material cost, direct labor cost, and factory overhead cost. Based on trial results on SMEs Shoes and Sandals Suroso can be concluded that the application has been made to produce information on the estimated raw material cost, the estimated direct labor cost, the estimated factory overhead cost, the estimated cost of goods manufactured, and reporting of customer order in each period, so the information can be used by SMEs as a basis for determining the selling price of its products.Keywords: cost of goods manufactured, estimated cost, customer order